Dual function of epaxial musculature for swimming and suction feeding in largemouth bass - Jimenez, Yordano E. (Proc Biol Sci, 2020)
The axial musculature of many fishes generates the power for both swimming and suction feeding. In the case of the epaxial musculature, unilateral activation bends the body laterally for swimming, and bilateral activation bends the body dorsally to elevate the neurocranium for suction feeding. But how does a single muscle group effectively power these two distinct behaviours? Prior electromyographic (EMG) studies have identified fishes' ability to activate dorsal and ventral epaxial regions independently, but no studies have directly compared the intensity and spatial activation patterns between swimming and feeding. We measured EMG activity throughout the epaxial musculature during swimming (turning, sprinting, and fast-starts) and suction feeding (goldfish and pellet strikes) in largemouth bass (Micropterus salmoides). We found that swimming involved obligate activation of ventral epaxial regions whereas suction feeding involved obligate activation of dorsal epaxial regions, suggesting regional specialization of the epaxial musculature. However, during fast-starts and suction feeding on live prey, bass routinely activated the whole epaxial musculature, demonstrating the dual function of this musculature in the highest performance behaviours. Activation intensities in suction feeding were substantially lower than fast-starts which, in conjunction with suboptimal shortening velocities, suggests that bass maximize axial muscle performance during locomotion and underuse it for suction feeding.